2014
DOI: 10.1016/j.jpainsymman.2013.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Creatively Caring: Effects of Arts-Based Encounters on Hospice Caregivers in South Africa

Abstract: International literature and experience suggest that arts-based encounters can be effective in reducing stress and burnout in health care workers. Are these principles universal? Are they as applicable and effective in resource-constrained situations in Africa as in other parts of the world? We describe the impact of creative and arts-based encounters on a group of hospice caregivers at South Coast Hospice in KwaZulu Natal. An experienced facilitator built a caring and trusting relationship with the participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Joslin et al [ 41 ], emphasised that managing psychological stress will lead to improved quality of life for nurses, financial benefits for the system, and improved patient care. Arts-based encounters can be effective in reducing stress and burnout in health care workers [ 78 ]. The research of Huss and Sarid [ 79 ], suggested that it is a timely moment to search for a short term and self-initiated arts based technique of stress reduction that will access health professionals’ creative recourses as an antidote to stress at work.…”
Section: Discussionmentioning
confidence: 99%
“…Joslin et al [ 41 ], emphasised that managing psychological stress will lead to improved quality of life for nurses, financial benefits for the system, and improved patient care. Arts-based encounters can be effective in reducing stress and burnout in health care workers [ 78 ]. The research of Huss and Sarid [ 79 ], suggested that it is a timely moment to search for a short term and self-initiated arts based technique of stress reduction that will access health professionals’ creative recourses as an antidote to stress at work.…”
Section: Discussionmentioning
confidence: 99%
“…The mere process of producing or performing art requires concentration and in this manner diverts the mind away from stressful thoughts, allowing for the basis of comparison between art and the therapeutic effect of mindfulness or meditation, which basically acts by providing a platform which is devoid of the main etiologies of stress (15). Although there is ground for belief that art-based interventions are effective in depressing the adverse physiological and psychological outcomes, the dimensions up to which these interventions improve health status is largely not deciphered (16).…”
Section: Discussionmentioning
confidence: 99%
“…20 One qualitative study noted 1 of 22 participants spoke of reduced burnout specifically. 22 No conclusion can be drawn as to whether or not poetry exclusively reduces professional burnout due to lack of studies.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the hospice caregivers noted decreased stress levels, greater ability to engage in their work, and one noted reduced professional burnout. 22 Adamson et al evaluated/assessed 1 group of 8 female nurses from an urban Canadian pediatric rehabilitation hospital who participated in six 90-minute weekly group narrative sessions (1 session was attended by 7 of the 8 nurses, otherwise all others fully attended) with semistructured interviews conducted pre and postintervention. Each session started with a short reading, such as a poem or comic, followed by a guided discussion with subsequent reflective writing or drawing which was then shared.…”
Section: Qualitative Studiesmentioning
confidence: 99%